1968
DOI: 10.1161/01.cir.38.5.941
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Central Venous Oxygen Saturation in Patients with Myocardial Infarction

Abstract: Central venous oxygen saturation (CVSO2) was measured in 31 patients with myocardial infarction. CVSO2 correlated well with the patients' clinical course. In those patients not in heart failure, mean + SEM for CVSO2 was 70 + 1%. When heart failure was present, CVSO2 averaged 56 + 1%. When both heart failure and shock were present, CVSO2 averaged 43 + 1%. In nine patients, serial determinations of arterial oxygen saturation and CVSO2 were made. In 22 of 26 instances, either a fall in CVSO2, was accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(22 citation statements)
references
References 2 publications
0
19
0
3
Order By: Relevance
“…Close correlation was found over a wide range of CO in patients with myocardial infarction admitted in a coronary care unit, and ScvO 2 measurement was helpful in assessing the direction of cardiac function and CO changes and monitoring drug therapy [12, 13]. Also, in an experimental study in dogs, Reinhart et al [1]found a high correlation between the two parameters during changes in oxygen supply/demand (r = 0.91–0.97) and that changes in ScvO 2 closely paralleled SvO 2 changes.…”
Section: Discussionmentioning
confidence: 99%
“…Close correlation was found over a wide range of CO in patients with myocardial infarction admitted in a coronary care unit, and ScvO 2 measurement was helpful in assessing the direction of cardiac function and CO changes and monitoring drug therapy [12, 13]. Also, in an experimental study in dogs, Reinhart et al [1]found a high correlation between the two parameters during changes in oxygen supply/demand (r = 0.91–0.97) and that changes in ScvO 2 closely paralleled SvO 2 changes.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, SvO 2 is tightly correlated with cardiac output and a drop in SvO 2 is a good and early marker of cardiac deterioration [15]. Correlation between SvO 2 and ScvO 2 was insufficient in patients with heart failure [8] but was reported to be accurate in patients with myocardial infarction [21]. Nevertheless, patients with congestive heart failure, who present high serum lactate levels and a low ScvO 2 , require a more aggressive management in the emergency department than patients with normal ScvO 2 and normal lactate levels [22].…”
Section: Severe Trauma and Hemorrhagic Shockmentioning
confidence: 99%
“…Although studies have established what normal central venous oxygen content is and how it varies in many clinical situations, there appears to be very little corresponding information on peripheral venous oxygen content [89,92,93,95,96]. An elevated peripheral venous oxygen content has been reported in multiple case reports of cyanide poisoning [63,80,82].…”
Section: How High Should Venous Oxygen Content Be To Help Make the DImentioning
confidence: 99%